Experiences of Folk Health Care Practice among People Suffered due to the unrest in the Southern Border Provinces - Arttanuchit, Sunida; Jeharsae, Rohani (Princess of Naradhiwas University Journal, 2019)
This qualitative research aims to explain meaning of health and folk health care experiences among people affected from unrest in the Southern Border Provinces (SBPs). The secondary data, verbatim transcription of in-depth 30 informants interview and focus group discussion, field notes and photographs from the field work practicum of nursing students for understanding of folk health care practices among people affected from the unrest in the SBPs were collected. Descriptive statistics was analyzed for describing characteristics of informants. Content analysis was done to explain the meaning of health and folk health care experiences among people affected from unrest in the SBPs. The study found that people affected from unrest explain the meaning of health as 1) health care practice 2) a sound mind in a sound body and 3) Supernatural power. Folk health care practices included 1) nutritional self-care practice 2) herbs and local wisdom 3) folk physical activities and 4) mental health and spiritual self-care and social interaction.